Pendampingan Reading Comprehension Menggunakan Komik Digital Di SMP Alquraniyah Nurul Huda Oku Timur - Hadziq Fikri, Arief; Zulaikah, Zulaikah; Julita, Nelya; Agustina, Eka; Haidorizal, Rifkan (IAI Darussalam, 2024)
The learning process would be effectively when supported by various planning, including the use and utilization of instructional media. Instructional media were employed to facilitate the process of understanding information and convey learning messages. Identifying the appropriate instructional media can influence the achievement of the teaching and learning process. SMP Alquraniyah Nurul Huda Martapura was a school unit that is relatively newly established, and thus, the teaching and learning process still requires methods that can support students' progress. The main issues identified in this community service activity were: 1) a lack of utilization of digital technology in delivering learning materials in the classroom, 2) the teaching process mostly relies on conventional methods, and 3) the English language background of the partners was weak. In addressing these challenges, the wrtiter utilized digital comic media, which considered more engaging for students due to its colorful and attractive visuals. The results achieved in this community service activity include a significant improvement in the reading skills of SMP Alquraniyah Nurul Huda students, as evidenced by their reading practice results after several days of learning to read Narrative Text using Digital Comic Media.